Obtención y caracterización de un material compuesto de matriz poliéster reforzado con pulverizado de madera de café (2022)
A biocomposite material was obtained and characterized from the polyester matrix and the reinforcement with pulverized coffee wood; motivated by a need to take advantage of the coffee wood waste, which reaches 338`086.000 kilos in the department of Huila. Starting from an experimental methodology, the coffee wood was prepared with its due drying, chip extraction, and sieving. A mixing was carried out at a temperature of 18 ºC with the following quantities: 16 g pulverized, 108 g polyester, 10 drops of cata specimens. 54 g polyester and 9 g pulverized were used for the tensile lyst in the flexural specimens. The results obtained from the laboratory and the use of the universal machine BESMAK, BMT ESeries; yielded a flexural value of 23,28 Mpa performed wi th the ASTM 790 standard and a tensile value of 19.71 Mpa with the ASTM D638 standard.